Difference of Vitamin D and Interleukin-6 Levels in Children with Steroid- Resistant, Steroid-Sensitive and Idiopathic Nephrotic Syndrome - Subandiyah, Krisni; Ghofar, Hervin Febrina; Fitri, Loeki Enggar (Journal of Tropical Life Science, 2019)
Idiopathic nephrotic syndrome (INS) is the most prevalent autoimmune glomerular disease in children and its pathogenesis is correlated with high level of interleukin 6 (IL-6) and low level of vitamin D. This study was aimed to investigate the difference of vitamin D and IL-6 level in steroid resistant nephrotic syndrome (SRNS), steroid sensitive (SSNS), and idiopathic nephrotic syndrome (INS). This research was designed as cross sectional involving 45 subjects which then divided into 3 groups as follows: SRNS, SSNS, and INS. A level of serum 25 (OH)D was measured by Enzyme-linked Immuno Assay Method then categorized as sufficiency, insufficiency, and deficiency. Level of IL-6 serum was measured by ELISA method. Results showed that IL-6 level was significantly different among three groups, in which SRNS had the highest value (ANOVA, p < 0.05). Further analysis demonstrated that IL-6 level correlated with steroid resistance (Spearman correlation test, p = 0.000, r = 0.692). Vitamin D status was significantly different among three groups (Chi square, p = 0.03) and associated with steroid resistance (Spearman correlation test, p = 0.000, r = 0.568). Moreover, IL-6 level associated with 25 (OH) D level in SRNS group (Pearson correlation test, p = 0.020, r = 0.591) but not in the SSNS and INS group. We conclude that IL-6 levels were significantly higher in SRNS group as compared to other groups. Otherwise, vitamin D status were significantly lower in SRNS compared with other groups. An IL-6 level was negatively correlated with vitamin D status in patients with NS, specifically in SRNS group.